Latex Compositions, Foams and Puffs
By incorporating silica with a specific surface area and amount into the latex composition, fine bubbles are formed during foam molding, addressing the issue of inadequate bubble formation and improving the performance of foam products.
Patent Information
- Application Number
- JP2020182496
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-10-30
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2040-10-30
AI Technical Summary
Existing latex compositions fail to form fine bubbles during foam molding, which is essential for achieving excellent absorption and drainage performance in applications like cosmetic sponges, leading to inadequate foam quality.
A latex composition is developed by adding silica with a BET specific surface area of 100 m²/g or less to a polymer latex, in an amount of 1 to 10 parts by weight, along with optional hydrophobization and other additives to enhance foam moldability and bubble formation.
The composition achieves excellent foam moldability and forms fine bubbles, resulting in improved absorption and drainage performance for liquid cosmetics, enhancing the quality of foam products.
Smart Images

Figure 0007615612000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a latex composition which has excellent foam moldability and is capable of forming fine cells during foam molding, and to a foam and a puff made using the same. [Background technology]
[0002] Latex compositions are used in foam (foam rubber) applications such as mattresses, puffs (cosmetic sponges), rolls, and shock absorbers. When used in foam applications, latex compositions are required to have excellent foaming properties, to foam uniformly, and to form foams with an excellent balance between elasticity and texture. In particular, when used in puffs to be impregnated with liquid cosmetics, etc., latex compositions are required to be capable of forming fine bubbles during foam molding in order to obtain foams with excellent suction and discharge performance for liquid cosmetics, etc.
[0003] For example, Patent Document 1 discloses a copolymer latex for cosmetic puffs, which is obtained by emulsion polymerization of 100 parts by weight in total of monomers consisting of 50-90% by weight of an aliphatic conjugated diene monomer, 10-50% by weight of a vinyl cyanide monomer, and 0-20% by weight of other monomers copolymerizable therewith, and which is characterized by having a solid content concentration of 60% by weight or more and a Mooney viscosity MS(1+4)100°C of 60-150. However, the technology of Patent Document 1 does not sufficiently reduce the size of bubbles during foam molding. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2006-181051 A Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a latex composition which has excellent foam moldability and is capable of forming fine cells during foam molding. [Means for solving the problem]
[0006] As a result of intensive research conducted by the present inventors in order to achieve the above object, 2 The present inventors have found that the above object can be achieved by a latex composition comprising a specific amount of silica having a silica content of 0.1 to 1000 nm, the silica content being ...
[0007] That is, according to the present invention, there is provided a latex composition comprising a polymer latex and silica added thereto, the silica having a BET specific surface area of 100 m 2 / g or less, and the amount of the silica added is 1 to 10 parts by weight per 100 parts by weight of the polymer component in the polymer latex.
[0008] In the latex composition of the present invention, the BET specific surface area of the silica is 5 to 75 m 2 It is preferred that the molecular weight is / g. In the latex composition of the present invention, the water content of the silica at a temperature of 23° C. and a relative humidity of 60% is preferably less than 7% by weight, and more preferably less than 5% by weight. In the latex composition of the present invention, the silica is preferably a dry process silica. In the latex composition of the present invention, the silica is preferably hydrophobized silica. The latex composition of the present invention preferably further contains a foam stabilizer.
[0009] According to the present invention, there is also provided a foam and a puff obtained by foam molding the latex composition of the present invention. Effect of the Invention
[0010] According to the present invention, it is possible to provide a latex composition which has excellent foam moldability and is capable of forming fine cells during foam molding. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The latex composition of the present invention is a polymer latex to which silica is added, and the BET specific surface area of the silica is 100 m 2 / g or less, and the amount of the silica added is 1 to 10 parts by weight based on 100 parts by weight of the polymer component in the polymer latex.
[0012] The polymer latex used in the present invention is a polymer dispersed in water. The polymer constituting the polymer latex is not particularly limited, but examples thereof include diene polymers, urethane polymers, acrylic polymers, fluorine polymers, and silicone polymers. Among these, from the viewpoint of the elasticity and durability of the resulting foam, diene polymers are preferred, and nitrile group-containing conjugated diene copolymers are particularly preferred. These polymers can be used alone or in combination of two or more.
[0013] The nitrile group-containing conjugated diene copolymer is a copolymer obtained by copolymerizing a conjugated diene monomer and an ethylenically unsaturated nitrile monomer, and may also be a copolymer obtained by copolymerizing, in addition to these, other ethylenically unsaturated monomers copolymerizable therewith, which are used as necessary.
[0014] The ethylenically unsaturated nitrile monomer is not particularly limited as long as it is an ethylenically unsaturated monomer containing a nitrile group, and examples thereof include acrylonitrile, methacrylonitrile, fumaronitrile, α-chloroacrylonitrile, α-cyanoethylacrylonitrile, etc. Among these, acrylonitrile and methacrylonitrile are preferred, and acrylonitrile is more preferred. These ethylenically unsaturated nitrile monomers can be used alone or in combination of two or more kinds.
[0015] The content of ethylenically unsaturated nitrile monomer units formed by ethylenically unsaturated nitrile monomers in the nitrile group-containing conjugated diene copolymer is more than 31% by weight, preferably 32 to 80% by weight, more preferably 33 to 70% by weight, and further preferably 34 to 60% by weight. By setting the content of the ethylenically unsaturated nitrile monomer units within the above range, the oil resistance and durability of the obtained foam can be improved.
[0016] Examples of the conjugated diene monomer include 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 1,3-pentadiene, and chloroprene. Among these, 1,3-butadiene and isoprene are preferred. These conjugated diene monomers can be used alone or in combination of two or more.
[0017] The content of the conjugated diene monomer units formed by the conjugated diene monomer in the nitrile group-containing conjugated diene copolymer is preferably less than 69% by weight, more preferably 20 to 68% by weight, even more preferably 30 to 67% by weight, and particularly preferably 40 to 66% by weight. By setting the content of the conjugated diene monomer units within the above range, the oil resistance and durability of the obtained foam can be improved.
[0018] From the viewpoint of improving the oil resistance and durability of the resulting foam, it is preferable to use both 1,3-butadiene and isoprene, and it is preferable that the ratio of 1,3-butadiene units to isoprene units in the nitrile group-containing conjugated diene copolymer is in the range of 5 / 5 to 9 / 1 in terms of the ratio of 1,3-butadiene units / isoprene units.
[0019] Examples of other ethylenically unsaturated monomers copolymerizable with the conjugated diene monomer and the ethylenically unsaturated nitrile monomer include ethylenically unsaturated carboxylic acids such as (meth)acrylic acid, (anhydrous) maleic acid, fumaric acid, and itaconic acid; mono- or di-alkyl esters of ethylenically unsaturated carboxylic acids such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, mono- or dimethyl maleate, mono- or diethyl fumarate, mono- or di-n-butyl fumarate, and mono- or di-n-butyl itaconate; and alkoxyalkyl esters of ethylenically unsaturated carboxylic acids such as methoxyacrylate, ethoxyacrylate, and methoxyethoxyethyl acrylate. Examples of the monomers include alkyl esters; (meth)acrylates having a hydroxyalkyl group such as 2-hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate; glycidyl (meth)acrylate; (meth)acrylamide, N-methylol (meth)acrylamide, and N-butoxymethyl (meth)acrylamide (meth)acrylamide and its derivatives; acrylates having an amino group such as dimethylaminomethyl acrylate and diethylaminomethyl acrylate; aromatic vinyl monomers such as styrene, α-methylstyrene, vinyltoluene, and chlorostyrene; α-olefins such as ethylene and propylene; and non-conjugated diene monomers such as dicyclopentadiene and vinylnorbornene. These monomers can be used alone or in combination of two or more. The content of other monomer units formed by other ethylenically unsaturated monomers in the nitrile group-containing conjugated diene copolymer is preferably 40% by weight or less, more preferably 30% by weight or less, and even more preferably 20% by weight or less. By setting the content of the other monomer units within the above range, the oil resistance and durability of the resulting foam can be improved.
[0020] The content ratio of the polymer component (solid content concentration) in the polymer latex used in the present invention is preferably 50% by weight or more, more preferably 55 to 70% by weight, and further preferably 60 to 70% by weight. By setting the content ratio of the polymer component within the above range, it is possible to improve the foaming power and gelling property. The content ratio of the polymer component can be adjusted, for example, by an operation of removing the solvent and a concentration treatment.
[0021] The polymer latex used in the present invention can be produced, for example, through a step of copolymerizing monomers constituting the polymer contained in the polymer latex by an emulsion polymerization method.
[0022] As the emulsion polymerization method, a conventionally known method can be adopted. For example, when emulsion polymerizing a monomer mixture, commonly used polymerization auxiliary materials such as an emulsifier (surfactant), a polymerization initiator, a chelating agent, an oxygen scavenger, and a molecular weight regulator can be used. The method of adding these polymerization auxiliary materials is not particularly limited, and any method such as an initial lump-sum addition method, a divided addition method, or a continuous addition method can be used.
[0023] The emulsifier is not particularly limited, and examples thereof include anionic emulsifiers and nonionic emulsifiers, with anionic emulsifiers being preferred. Examples of the anionic emulsifier include fatty acid salts such as potassium tallow fatty acid, partially hydrogenated potassium tallow fatty acid, potassium oleate, and sodium oleate; resin acid salts such as potassium rosinate, sodium rosinate, potassium hydrogenated rosinate, and sodium hydrogenated rosinate; and alkylbenzene sulfonate salts such as sodium dodecylbenzene sulfonate. Examples of the nonionic emulsifier include emulsifiers of polyethylene glycol ester type and Pluronic type such as block copolymers of ethylene oxide and propylene oxide. Among these, anionic emulsifiers are preferred, fatty acid salts are more preferred, and potassium oleate and sodium oleate are even more preferred. The amount of the emulsifier used is preferably 0.5 to 5 parts by weight relative to 100 parts by weight of the monomer mixture.
[0024] The polymerization initiator is not particularly limited, but examples thereof include inorganic peroxides such as sodium persulfate, potassium persulfate, ammonium persulfate, potassium perphosphate, and hydrogen peroxide; organic peroxides such as diisopropylbenzene hydroperoxide, cumene hydroperoxide, t-butyl hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, 2,5-dimethylhexane-2,5-dihydroperoxide, di-t-butyl peroxide, di-α-cumyl peroxide, acetyl peroxide, isobutyryl peroxide, benzoyl peroxide, octanoyl peroxide, and 3,5,5-trimethylhexanoyl peroxide; and azo compounds such as azobisisobutyronitrile, azobis-2,4-dimethylvaleronitrile, and methyl azobisisobutyrate. These polymerization initiators can be used alone or in combination of two or more. The amount of the polymerization initiator used is preferably 0.01 to 10 parts by weight, more preferably 0.01 to 2 parts by weight, based on 100 parts by weight of the monomer mixture.
[0025] The peroxide initiator can be used as a redox polymerization initiator in combination with a reducing agent. The reducing agent is not particularly limited, but includes compounds containing reduced metal ions such as ferrous sulfate and cuprous naphthenate; sulfonic acid compounds such as sodium methanesulfonate; and amine compounds such as dimethylaniline. These reducing agents can be used alone or in combination of two or more. The amount of the reducing agent used is preferably 3 to 1000 parts by weight per 100 parts by weight of the peroxide.
[0026] Examples of the molecular weight regulator include alkyl mercaptans such as n-hexyl mercaptan, n-octyl mercaptan, t-octyl mercaptan, n-dodecyl mercaptan, t-dodecyl mercaptan, and n-stearyl mercaptan; xanthogen compounds such as dimethyl xanthogen disulfide and diisopropyl xanthogen disulfide; thiuram compounds such as tetramethylthiuram disulfide, tetraethylthiuram disulfide, and tetramethylthiuram monosulfide; 2,6-di-t-butyl-4- Examples of the molecular weight regulator include phenolic compounds such as methylphenol and styrenated phenol; allyl compounds such as allyl alcohol; halogenated hydrocarbon compounds such as dichloromethane, dibromomethane, and carbon tetrabromide; α-benzyloxystyrene, α-benzyloxyacrylonitrile, α-benzyloxyacrylamide, triphenylethane, pentaphenylethane, acrolein, methacrolein, thioglycolic acid, thiomalic acid, 2-ethylhexylthioglycolate, α-methylstyrene dimer, and terpinolene. These molecular weight regulators can be used alone or in combination of two or more kinds. The amount of the molecular weight regulator used is preferably 0.1 to 3 parts by weight, more preferably 0.2 to 2 parts by weight, and particularly preferably 0.3 to 1.5 parts by weight, based on 100 parts by weight of the monomer mixture.
[0027] The amount of water used in emulsion polymerization is preferably from 80 to 600 parts by weight, particularly preferably from 100 to 300 parts by weight, based on 100 parts by weight of the total monomers used.
[0028] The emulsion polymerization reaction may be either continuous or batchwise, and the polymerization time is not particularly limited. The monomer addition method may include, for example, a method of adding the monomers to be used in a reaction vessel all at once, a method of adding them continuously or intermittently as the polymerization proceeds, a method of adding a part of the monomers and reacting them to a specific conversion rate, and then adding the remaining monomers continuously or intermittently to polymerize them, and any of these methods may be adopted. When the monomers are mixed and added continuously or intermittently, the composition of the mixture may be constant or may be changed. In addition, the various monomers to be used may be mixed in advance and then added to the reaction vessel, or each monomer may be added to the reaction vessel separately.
[0029] Furthermore, when carrying out emulsion polymerization, polymerization auxiliary materials such as a chelating agent, a dispersing agent, a pH adjuster, an oxygen scavenger, a particle size adjuster, etc. can be used as necessary, and the type and the amount of these to be used are not particularly limited.
[0030] As described above, the monomer mixture is emulsion-polymerized, and when a predetermined polymerization conversion rate is reached, the polymerization reaction is stopped by cooling the polymerization system or adding a polymerization terminator. The polymerization conversion rate at the time of stopping the polymerization is not particularly limited, but is preferably 90% by weight or more. If this polymerization conversion rate is too low, the productivity tends to decrease. The polymerization temperature is not particularly limited, but is preferably 0 to 50°C, more preferably 2 to 35°C.
[0031] The polymerization terminator is not particularly limited, but examples thereof include hydroxylamine, hydroxylamine sulfate, diethylhydroxylamine, hydroxylamine sulfonic acid and its alkali metal salts, sodium dimethyldithiocarbamate, hydroquinone derivatives, catechol derivatives, and aromatic hydroxydithiocarboxylic acids such as hydroxydimethylbenzenethiocarboxylic acid, hydroxydiethylbenzenedithiocarboxylic acid, and hydroxydibutylbenzenedithiocarboxylic acid, and their alkali metal salts. The amount of the polymerization terminator used is preferably 0.05 to 2 parts by weight based on 100 parts by weight of the monomer mixture.
[0032] The polymerization reaction is carried out as described above to obtain an emulsion. After the polymerization reaction is terminated to obtain an emulsion, unreacted monomers may be removed from the emulsion, if necessary.
[0033] After the polymerization reaction is terminated, the volume cumulative particle size of the polymer particles contained in the resulting emulsion may be further adjusted.
[0034] Methods for adjusting the volume cumulative particle size include (i) a method of subjecting particles in an emulsion to a particle size enlarging treatment in which the particles are enlarged by coalescing with each other, (ii) a method of coagulating the particles contained in an emulsion to obtain a coagulate, dissolving the coagulate in an organic solvent to obtain a solution, emulsifying the obtained solution in water in the presence of an emulsifier, and removing the organic solvent as necessary, and (iii) a method of mixing two or more emulsions having different volume cumulative particle sizes.
[0035] In the method (i), the method of particle size enlargement treatment is not particularly limited, but examples thereof include (1) a method in which a conjugated diene compound such as 1,3-butadiene or toluene is added as a solvent to the emulsion after the completion of polymerization, and the mixture is vigorously stirred, and (2) a method in which a particle size enlargement agent such as a carboxyl group-containing polymer latex is added to the emulsion, and the mixture is vigorously stirred.
[0036] When the particle size enlargement treatment is performed by the above method (1), the amount of the solvent added is preferably 30 to 300 parts by weight relative to 100 parts by weight of the nitrile group-containing conjugated diene copolymer in the emulsion. When the particle size enlargement treatment is performed by the above method (1), the stirring conditions are not particularly limited, but examples thereof include a method using a stirring device such as a paddle-type stirring blade, with a rotation speed of preferably 50 to 2,500 rpm and a stirring time of preferably 0.5 to 12.0 hours.
[0037] In addition, when carrying out the particle size enlargement treatment, from the viewpoint of suppressing foaming due to stirring, it is preferable to add an antifoaming agent to the emulsion and carry out the particle size enlargement treatment in the presence of the antifoaming agent.
[0038] In the method (ii), examples of the method for coagulating the particles contained in the emulsion include a method of mixing the emulsion with a water-soluble organic solvent, a method of mixing the emulsion with an acid, and a method of mixing the emulsion with a salt.
[0039] As the water-soluble organic solvent, it is more preferable to select a solvent in which the polymer in the latex does not dissolve. Examples of such organic solvents include methanol, ethanol, isopropyl alcohol, and ethylene glycol. Examples of acids include acetic acid, formic acid, phosphoric acid, and hydrochloric acid. Examples of salts include calcium chloride, sodium chloride, aluminum sulfate, and potassium chloride.
[0040] Examples of the organic solvent used in method (ii) include aromatic hydrocarbon solvents such as benzene, toluene, xylene, etc.; alicyclic hydrocarbon solvents such as cyclopentane, cyclopentene, cyclohexane, cyclohexene, etc.; aliphatic hydrocarbon solvents such as pentane, hexane, heptane, etc.; halogenated hydrocarbon solvents such as methylene chloride, chloroform, ethylene dichloride, etc.; ketone-based solvents such as acetone, methyl ethyl ketone, diethyl ketone, diisopropyl ketone, methyl isobutyl ketone, methyl hexyl ketone, diisobutyl ketone, butyl aldehyde, propyl acetate, butyl acetate, amyl acetate, etc.; ester-based solvents such as ethyl propionate, ethyl isobutyrate, butyl butyrate, etc.; ether-based solvents such as dimethyl ether, dihexyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, etc.
[0041] In the method (ii), an emulsifying apparatus can be used to emulsify the obtained solution in water in the presence of an emulsifier. The method of adding the emulsifier is not particularly limited, and the emulsifier may be added to the solution in advance, or may be added to the solution during the emulsification operation, or may be added all at once or in portions.
[0042] The emulsifier used in the method (ii) may be an anionic emulsifier, a nonionic emulsifier, or the like, with an anionic emulsifier being preferred. As the anionic emulsifier, the one mentioned above as the anionic emulsifier that may be contained in the latex may be used. The amount of the emulsifier used is preferably 0.5 to 50 parts by weight, more preferably 0.5 to 30 parts by weight, and even more preferably 5 to 25 parts by weight, relative to 100 parts by weight of the particles. By appropriately adjusting the amount of the emulsifier used, the volume cumulative particle size can be adjusted to a desired range.
[0043] In the method (ii), examples of the method for removing the organic solvent include reduced pressure distillation, atmospheric distillation, steam distillation, and centrifugation.
[0044] In the method (iii), two or more emulsions may be mixed to obtain a desired volume cumulative particle size, and the mixing method is not particularly limited. The combination of emulsions is also not limited, and for example, two emulsions obtained by the method (i) with different volume cumulative particle sizes may be mixed, or two emulsions obtained by the method (ii) with different volume cumulative particle sizes may be mixed. In addition, the emulsion obtained by polymerization may be mixed with the emulsion obtained by the methods (i) and / or (ii) by a known method, or the emulsion obtained by the method (i) may be mixed with the emulsion obtained by the method (ii).
[0045] The latex composition of the present invention has a BET specific surface area of 100 m 2 / g or less of silica is added to a polymer latex.
[0046] The BET specific surface area of the silica used in the present invention is 100 m 2 If the BET specific surface area of the silica is too large, it becomes difficult to form fine bubbles during foaming. The BET specific surface area of the silica used in the present invention is 100 m 2 / g or less, but is not particularly limited thereto, and the range is from 3 to 75 m 2 / g, and 5 to 60m 2 / g is more preferable, and 7 to 50m 2 More preferably, it is 10 to 40 m / g. 2 / g is particularly preferred, and 15 to 35m 2 / g is the most preferable. The BET specific surface area is a specific surface area measured by a gas adsorption method based on the BET theory. When measuring the BET specific surface area, a gas that is usually used for measuring the BET specific surface area may be used as the adsorption gas, and nitrogen gas is preferable as the adsorption gas.
[0047] The silica is not particularly limited, and examples thereof include dry process silica such as combustion process silica and arc process silica; and wet process silica such as precipitation process silica and sol-gel process silica. Among these, dry process silica or sol-gel process silica is preferred, and from the viewpoint of foam moldability, dry process silica is more preferred.
[0048] As the silica, hydrophobized silica, in which the silanol group on the silica surface is modified with a hydrophobic group, is preferred.By using the hydrophobized silica, the stability of the bubbles generated during foaming of the latex composition can be improved, and as a result, the latex composition has better foaming moldability and can form finer bubbles during foaming.The hydrophobized silica may be one in which a part of the hydrophilic group on the silica surface is modified with a hydrophobic group, or one in which all of the hydrophilic groups on the silica surface are modified with a hydrophobic group.
[0049] Examples of hydrophobic groups for forming the hydrophobized silica include a dimethylsilyl group, a trimethylsilyl group, a trimethylsiloxy group, a dimethylpolysiloxane group, a dimethylsiloxane group, an aminoalkylsilyl group, an alkylsilyl group, and a methacrylsilyl group. Among these, a trimethylsilyl group, a trimethylsiloxy group, or a dimethylpolysiloxane group is preferred, and a trimethylsilyl group or a dimethylpolysiloxane group is more preferred.
[0050] The moisture content of silica is not particularly limited, but the moisture content of silica at a temperature of 23°C and a relative humidity of 60% is preferably less than 7% by weight, more preferably less than 5% by weight, even more preferably 3.5% by weight or less, and particularly preferably 2.5% by weight or less. By using silica having a moisture content within the above range, finer bubbles can be formed during foaming of the latex composition. The lower limit of the moisture content of silica at a temperature of 23°C and a relative humidity of 60% is not particularly limited, but is usually 0.01% by weight or more, preferably 0.1% by weight or more. The moisture content of silica at a temperature of 23°C and a relative humidity of 60% can be determined by a loss on drying method (for example, a method of measuring weight change by infrared heating dry mass measurement). Specifically, it can be determined by the method described in the examples below.
[0051] The pH of the silica is not particularly limited, but is preferably 10 or less, more preferably 3-9, and even more preferably 3.5-8.
[0052] In the latex composition of the present invention, the amount of silica added is 1 to 10 parts by weight relative to 100 parts by weight of the polymer component in the polymer latex. If the amount of silica added is too large, the foaming moldability is poor, such as poor handling during foaming or poor shrinkage resistance. On the other hand, if the amount of silica added is too small, it becomes difficult to form fine bubbles during foaming. The amount of silica added may be 1 to 10 parts by weight relative to 100 parts by weight of the polymer component in the polymer latex, and is not particularly limited, but is preferably 1 to 9 parts by weight, more preferably 1 to 8 parts by weight, and even more preferably 1 to 7 parts by weight relative to 100 parts by weight of the polymer component, thereby making the latex composition more excellent in foaming moldability and capable of forming finer bubbles during foaming.
[0053] The latex composition of the present invention may further contain an anionic surfactant. Examples of the anionic surfactant include fatty acid salts such as potassium tallow fatty acid, partially hydrogenated potassium tallow fatty acid, potassium oleate, and sodium oleate; resin acid salts such as potassium rosinate, sodium rosinate, potassium hydrogenated rosinate, and sodium hydrogenated rosinate; and alkylbenzene sulfonate salts such as sodium dodecylbenzene sulfonate. Among these, fatty acid salts are preferred, and potassium oleate and sodium oleate are more preferred. These can be used alone or in combination of two or more. The content of the anionic surfactant is preferably 0.5 to 5 parts by weight based on 100 parts by weight of the polymer component in the latex composition.
[0054] The latex composition of the present invention preferably further contains a foam stabilizer. The foam stabilizer is not particularly limited, but examples thereof include reaction products obtained by reacting an alkyl chloride such as ethyl chloride with formaldehyde and ammonia, such as ethyl chloride-formaldehyde-ammonia reaction products; alkyl quaternary ammonium chlorides; alkylarylsulfonates; and higher fatty acid ammonium salts. Among these, ethyl chloride-formaldehyde-ammonia reaction products are preferred. These can be used alone or in combination of two or more. The content of the foam stabilizer is preferably 0.5 to 5 parts by weight, more preferably 1 to 5 parts by weight, based on 100 parts by weight of the polymer component in the latex composition.
[0055] The latex composition of the present invention preferably further contains a crosslinking agent. Examples of the crosslinking agent include sulfur such as powdered sulfur, sulfur flowers, precipitated sulfur, colloidal sulfur, surface-treated sulfur, and insoluble sulfur; sulfur chloride, sulfur dichloride, morpholine disulfide, alkylphenol disulfide, N,N'-dithio-bis(hexahydro-2H-azepinone-2), phosphorus-containing polysulfide, polymeric polysulfide, and sulfur-containing compounds such as 2-(4'-morpholinodithio)benzothiazole. Among these, sulfur is preferably used. The crosslinking agent may be used alone or in combination of two or more. The content of the crosslinking agent is not particularly limited, but is preferably 0.1 to 10 parts by weight, more preferably 0.2 to 3 parts by weight, based on 100 parts by weight of the polymer in the polymer latex. By setting the content of the crosslinking agent within the above range, the strength of the obtained foam can be increased.
[0056] The latex composition of the present invention preferably further contains a crosslinking accelerator. As the crosslinking accelerator, those generally used in the production of foams can be used, for example, dithiocarbamic acids such as diethyldithiocarbamic acid, dibutyldithiocarbamic acid, di-2-ethylhexyldithiocarbamic acid, dicyclohexyldithiocarbamic acid, diphenyldithiocarbamic acid, dibenzyldithiocarbamic acid, and zinc salts thereof; 2-mercaptobenzothiazole, 2-mercaptobenzothiazole zinc, 2-mercaptothiazoline, dibenzothiazyl disulfide, 2-(2, Examples of the crosslinking accelerator include 4-dinitrophenylthio)benzothiazole, 2-(N,N-diethylthio carbylthio)benzothiazole, 2-(2,6-dimethyl-4-morpholinothio)benzothiazole, 2-(4'-morpholinodithio)benzothiazole, 4-morpholinyl-2-benzothiazyl disulfide, and 1,3-bis(2-benzothiazyl mercaptomethyl)urea, but zinc diethyldithiocarbamate, zinc dibutyldithiocarbamate, and zinc 2-mercaptobenzothiazole are preferred. The crosslinking accelerator may be used alone or in combination of two or more. The content of the crosslinking accelerator is preferably 0.1 to 5 parts by weight, more preferably 0.2 to 4 parts by weight, based on 100 parts by weight of the polymer in the polymer latex. By setting the content of the crosslinking accelerator within the above range, the strength of the resulting foam can be increased.
[0057] The latex composition of the present invention preferably further contains zinc oxide. The content of zinc oxide is not particularly limited, but is preferably 0.5 to 10 parts by weight, more preferably 0.5 to 8 parts by weight, based on 100 parts by weight of the polymer in the polymer latex. By setting the content of zinc oxide within the above range, it is possible to improve the strength of the obtained foam while improving the emulsion stability.
[0058] The latex composition of the present invention may further contain, as required, an antioxidant, a colorant, an ultraviolet absorbing agent, and a dispersing agent for stably dispersing the above-mentioned various compounding agents in the latex (for example, NASF (sodium salt of naphthalenesulfonic acid-formalin condensate)), a thickening agent (for example, polyacrylic acid and its sodium salt, sodium alginate, polyvinyl alcohol, etc.), and a surfactant as a foaming agent (for example, an aliphatic alkali soap such as potassium oleate, a sulfate of higher alcohol such as sodium dodecyl sulfate, etc.).
[0059] The method for producing the latex composition is not particularly limited, but examples thereof include a method of mixing silica and various compounding agents to be mixed as necessary with a polymer latex using a dispersing machine such as a ball mill, kneader, or disperser, and a method of preparing an aqueous dispersion of compounding components other than the polymer latex using the above-mentioned dispersing machine, and then mixing the aqueous dispersion with the polymer latex. Also, silica and various compounding agents may be added to the polymer latex before foaming the polymer latex, or silica and various compounding agents may be added to the foamed polymer latex after foaming the polymer latex, or these may be combined.
[0060] The latex composition of the present invention has excellent foam moldability and can form fine bubbles during foam molding, and therefore can be suitably used for the production of foams (foam rubber). That is, the latex composition of the present invention is preferably a latex composition for foam rubber.
[0061] The latex composition of the present invention can be foamed at a desired expansion ratio, coagulated, and foam-molded to obtain the foam of the present invention.
[0062] Air is usually used for foaming, but gas generating substances such as carbonates such as ammonium carbonate and sodium bicarbonate, azo compounds such as azodicarboxylic acid amide and azobisisobutyronitrile, and benzenesulfonyl hydrazide can also be used. When air is used, the latex composition can be foamed by stirring and incorporating air. In this case, for example, an Oaks foaming machine or an ultrasonic foaming machine can be used.
[0063] After foaming the latex composition, the foamed latex composition is coagulated in order to fix the foamed state. The coagulation method may be any method capable of gelling and solidifying the latex, and any conventionally known method may be used. For example, the Dunlop method (room temperature coagulation method) in which a room temperature coagulant such as sodium hexafluorosilicate (sodium silicofluoride), potassium hexafluorosilicate (potassium silicofluoride), or a silicon fluoride compound such as titanium sodium silicofluoride is added to the foamed latex composition; the heat-sensitive coagulation method in which a heat-sensitive coagulant such as organopolysiloxane, polyvinyl methyl ether, or zinc ammonium sulfate complex salt is added to the foamed latex composition; or the freeze coagulation method may be used. The amount of the coagulant such as the room temperature coagulant or the heat-sensitive coagulant is not particularly limited, but is preferably 0.5 to 10 parts by weight, more preferably 0.5 to 8 parts by weight, based on 100 parts by weight of the polymer component in the latex composition.
[0064] Then, after adding a coagulant to the foamed latex composition, the composition is transferred to a mold of a desired shape and coagulated to obtain a foam. After coagulation, the latex composition may be heated to crosslink. The crosslinking conditions are preferably a temperature of 100 to 160°C and a heat treatment time of preferably 15 to 120 minutes.
[0065] The obtained foam is preferably washed after being removed from the mold. The washing method is not particularly limited, but may be, for example, a method of washing with water at about 20 to 70°C using a washing machine or the like and stirring for about 5 to 15 minutes. After washing, it is preferable to drain the water and dry at a temperature of about 30 to 90°C so as not to damage the texture of the foam. The foam thus obtained can be used as a puff (cosmetic sponge) or the like by, for example, slicing it to a predetermined thickness and cutting it into a predetermined shape, and then grinding the sides with a rotating grindstone or the like.
[0066] The foam of the present invention can be suitably used for various applications such as mattresses, puffs (cosmetic sponges), rolls, shock absorbers, etc. In particular, since the foam of the present invention is obtained using the latex composition of the present invention, it has fine bubbles and is excellent in terms of absorbing and discharging liquid cosmetics and the like, and therefore can be suitably used as a puff (cosmetic sponge) to be impregnated with liquid cosmetics and the like. EXAMPLES
[0067] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the following, unless otherwise specified, "parts" are based on weight. The methods for testing or evaluating physical properties and characteristics are as follows.
[0068] <Solids concentration of polymer latex> 2 g of the sample was weighed out (weight: X2) onto an aluminum dish (weight: X1), and dried for 2 hours in a hot air dryer at 105° C. Then, after cooling in a desiccator, the weight of the aluminum dish was measured (weight: X3), and the solid content was calculated according to the following formula. Solid content concentration (wt%)=(X3-X1)×100 / X2
[0069] <Water content of silica> The silica was heated at 120°C for 2 hours, and then placed in a moisture meter (model "MOC-120H", manufactured by Shimadzu Corporation) installed in a room at a temperature of 23°C and a relative humidity of 60%, and then left to stand for 15 hours under the conditions of a temperature of 23°C and a relative humidity of 60%, and the water content of the silica (W wet Next, the water weight (W wet The silica whose dry weight (W dry The measured water weight (W wet ) and dry weight (W dry ) and the moisture content of silica was calculated based on the following formula: Water content of silica (wt%) = (W wet -W dry )÷W wet ×100
[0070] <Handling> The handleability of the latex composition was evaluated by visual observation according to the following criteria: The better the handleability, the better the foam moldability of the latex composition. ◯: The latex composition had good dispersibility and was in a state suitable for foam molding. ×: The latex state was not maintained and foam molding was not possible.
[0071] <Shrinkage resistance during molding> The latex composition was stirred using a stand mixer (model "ESM945", manufactured by Electrolux) and foamed to about 5 times its volume, after which an aqueous dispersion of sodium silicofluoride (solid concentration 20% by weight) was added so that the sodium silicofluoride was 1.5 parts per 100 parts by weight of the polymer component in the latex composition, and the mixture was further stirred for 1 minute to obtain a foam. The gelling foam was poured into a petri dish to a predetermined height (i.e., the height of the foam before crosslinking) and crosslinked at 110°C for 40 minutes, the height of the crosslinked product was measured, and the shrinkage rate was calculated using the following formula. Shrinkage rate (%) = [(height of cross-linked product) - (height of foam before cross-linking)] / (height of foam before cross-linking) x 100 Based on the shrinkage percentage obtained as above, the shrinkage resistance during molding was evaluated according to the following criteria. The better the shrinkage resistance during molding, the more excellent the foam moldability of the latex composition. ⊚: The shrinkage rate was -5% or more and 0% or less. Good: The shrinkage rate was -15% or more and less than -5%. ×: The shrinkage rate was −100% or more and less than −15%.
[0072] <Bubble volume> The foam was photographed using an X-ray computed tomography apparatus (X-ray apparatus, manufactured by Yamato Scientific Co., Ltd.), and the median bubble volume per bubble (median value in the volume distribution based on number) was determined.
[0073] <Example 1> A pressure-resistant reactor was charged with 200 parts of water, 1.5 parts of potassium oleate, 38 parts of acrylonitrile, 0.5 parts of t-dodecyl mercaptan, 0.03 parts of sodium formaldehyde sulfoxylate, 0.003 parts of ferrous sulfate, and 0.008 parts of sodium ethylenediaminetetraacetate, and after sufficient degassing, 45 parts of 1,3-butadiene and 17 parts of isoprene were added.
[0074] Next, 0.05 parts of cumene hydroperoxide was added as a polymerization initiator to initiate emulsion polymerization at a reaction temperature of 5° C. When the polymerization conversion rate reached 95%, a polymerization terminator solution consisting of 0.25 parts of diethylhydroxylamine and 5 parts of water was added to terminate the polymerization reaction, thereby obtaining an emulsion.
[0075] Next, 80 parts of 1,3-butadiene was added to the emulsion as a solvent, the temperature in the system was set to 15°C, and the mixture was strongly stirred at a rotation speed of 1,000 rpm and a stirring time of 5 hours using a paddle-type stirring blade to perform particle size enlargement treatment. Next, after removing 1,3-butadiene, concentration treatment was performed at 70°C under reduced pressure conditions of -0.05 MPa (gauge pressure) to obtain a latex of a nitrile group-containing conjugated diene copolymer.
[0076] The content of ethylenically unsaturated nitrile monomer units in the obtained latex was measured according to the above-mentioned method, and was found to be 36% by weight. The solid content of the obtained latex of the nitrile group-containing conjugated diene copolymer was 66% by weight.
[0077] The latex of the nitrile group-containing conjugated diene copolymer obtained above was mixed with 100 parts of the polymer component in the latex, and a trimethylsilyl group-treated dry process silica (product name "AEROSIL (registered trademark) NAX 50", manufactured by Nippon Aerosil Co., Ltd., BET specific surface area 50 m) was added. 2 3 parts of 1.6% water content at 23°C and 60% relative humidity, 3 parts of aqueous vulcanization system dispersion (colloidal sulfur / dithiocarbamate vulcanization accelerator Noccelaer EZ (Ouchi Shinko Chemical Industry Co., Ltd.) / thiazole vulcanization accelerator Noccelaer MZ (Ouchi Shinko Chemical Industry Co., Ltd.) = 2 / 1 / 1 (weight ratio), solid content concentration 50% by weight), 4 parts of aqueous zinc oxide dispersion (solid content concentration 50% by weight), 3 parts of aqueous zinc oxide dispersion (solid content concentration 50% by weight), and 1 part of foam stabilizer (Trimenbase: Crompton Corp.) were added and thoroughly dispersed to obtain a latex composition. The obtained latex composition was evaluated for handleability and shrinkage resistance during molding according to the above-mentioned method. The results are shown in Table 1.
[0078] The latex composition was stirred using a stand mixer (model "ESM945", manufactured by Electrolux) and foamed to about 5 times its volume, and then 1.5 parts of sodium silicofluoride aqueous dispersion (solid content concentration 20% by weight) was added to 100 parts of the latex composition polymer component, and the mixture was further stirred for 1 minute to obtain a foam.
[0079] The foam obtained was then poured into a molding frame (diameter 7 cm, height 8 cm), solidified, and then vulcanized by heating at 110°C for 1 hour, then removed from the frame, washed with 40°C water for 10 minutes, dried in an oven at 60°C for 4 hours, and cut to a thickness of 0.8 cm in the height direction to obtain a disk-shaped foam. The bubble volume of the obtained foam was then measured according to the above method. The results are shown in Table 1.
[0080] <Examples 2 to 5> Except for changing the type of silica to the type shown in Table 1 and changing the amount of silica added to the amount shown in Table 1, a latex composition and a foam were obtained in the same manner as in Example 1, and were evaluated and measured in the same manner as in Example 1. The results are shown in Table 1.
[0081] <Comparative Example 1> Instead of 3 parts of the dry-process silica treated with trimethylsilyl groups, a dry-process silica not treated for hydrophobization (product name "AEROSIL (registered trademark) 200" manufactured by Nippon Aerosil Co., Ltd., BET specific surface area 200 m) was used. 2 A latex composition and a foam were obtained in the same manner as in Example 1, except that 3 parts of 1,2-difluorophenyl ether (1,2-difluorophenyl ether) was used, and the latex composition and the foam were evaluated and measured in the same manner as in Example 1. The results are shown in Table 1.
[0082] <Comparative Example 2> Except for not adding 3 parts of the dry process silica treated with trimethylsilyl groups, a latex composition and a foam were obtained in the same manner as in Example 1, and were evaluated and measured in the same manner as in Example 1. The results are shown in Table 1.
[0083] [Table 1] (※) The types of silica are as follows. AEROSIL NAX 50: Trimethylsilyl-treated dry process silica (product name "AEROSIL (registered trademark) NAX 50", manufactured by Nippon Aerosil Co., Ltd., BET specific surface area 50 m 2 / g, moisture content 1.6% by weight at 23°C and 60% relative humidity AEROSIL NY 50: Dimethylpolysiloxane-treated dry process silica (product name "AEROSIL (registered trademark) NY 50", manufactured by Nippon Aerosil Co., Ltd., BET specific surface area 30 m 2 / g, moisture content 1.6% by weight at 23°C and 60% relative humidity AEROSIL OX 50: Dry process silica that has not been hydrophobized (product name "AEROSIL (registered trademark) OX 50", manufactured by Nippon Aerosil Co., Ltd., BET specific surface area 50 m 2 / g, moisture content 2.0% by weight at 23°C and 60% relative humidity QSG-100: Trimethylsiloxy-treated sol-gel silica (product name "QSG-100", manufactured by Shin-Etsu Chemical Co., Ltd., BET specific surface area 25 m 2 / g, moisture content 5.5% by weight at 23°C and 60% relative humidity AEROSIL 200: Dry process silica that has not been hydrophobized (product name "AEROSIL (registered trademark) 200", manufactured by Nippon Aerosil Co., Ltd., BET specific surface area 200 m 2 / g, moisture content 3.6% at 23°C and 60% relative humidity
[0084] As shown in Table 1, the BET specific surface area is 100 m 2 The latex composition obtained by adding a specific amount of silica having a molecular weight of 0.01 to 0.1 g / g or less to the polymer latex had excellent foam moldability and was capable of forming fine bubbles during foam molding (Examples 1 to 5).
[0085] On the other hand, when the BET specific surface area of the silica was too large or when no silica was added, fine cells could not be formed during foam molding (Comparative Examples 1 and 2).
Claims
1. A latex composition comprising a polymer latex, silica and a foam stabilizer added thereto, The BET specific surface area of the silica is 100 m 2 / g or less, The amount of the silica added is 1 to 10 parts by weight based on 100 parts by weight of the polymer component in the polymer latex.
2. The BET specific surface area of the silica is 5 to 75 m 2 2. The latex composition of claim 1, wherein the molecular weight of the latex is 1 / g.
3. 3. The latex composition according to claim 1, wherein the silica has a moisture content of less than 7% by weight at a temperature of 23° C. and a relative humidity of 60%.
4. 4. The latex composition according to claim 1, wherein the silica has a moisture content of less than 5% by weight at a temperature of 23° C. and a relative humidity of 60%.
5. 5. The latex composition according to claim 1, wherein the silica is a dry process silica.
6. 6. The latex composition according to claim 1, wherein the silica is a hydrophobically treated silica.
7. A foam obtained by foam molding the latex composition according to any one of claims 1 to 6.
8. A puff obtained by foam molding the latex composition according to any one of claims 1 to 6.
Citation Information
Patent Citations
High-strength silicone rubber granule and production thereof
JP1992168117A
Emulsion-type defoaming agent composition and defoaming method using the same
JP1994039207A
Production of water-base composition based on fluoroelastomer for thick film
JP1995090088A
Latex foam and method for producing the same
JP2003192824A
Copolymer latex for makeup puff
JP2006181051A